HIV/AIDS as a Fiscal Liability - Markus Haacker (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
The costs of HIV/AIDS programs are significant from a macroeconomic or fiscal perspective in a number of countries. Assessing the fiscal implications is complicated by the long lags between infection and the need for HIV/AIDS-related services, and the long duration over which these services (notably treatment) are required. The paper interprets the fiscal costs of HIV/AIDS programs as quasi-liabilities, which are incurred by HIV infections and are paid off as HIV/AIDS-related services are delivered. On the microeconomic level, the analysis yields estimates of the costs incurred by single HIV infections, which - together with other criteria - can be used in assessing the effectiveness of HIV/AIDS program allocations. On the macroeconomic level, the analysis highlights the large magnitude of the HIV/AIDS quasi-liability (according to criteria for the sustainability of public debt), and quantifies the fiscal savings achieved or projected as a consequence of declining HIV incidence.
Keywords: H5; H6; I1; 330; HIV/AIDS; health shocks; health expenditures; social expenditures; fiscal space; debt sustainability; quasi-liabilities; Africa; Botswana; South Africa; Swaziland; Uganda